Effectiveness of Garra Rufa Care Toward Pruritus Elderly Who Live in Indonesian Village - Zagad Budhi Dharma1 , Joni Haryanto2 , Elida Ulfiana2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pruritus is a neuordegeneratif disease that attacks the peripheral skin. It is not infrequently the elderly experience these health problems with itching complaint, so that it cause a feeling of wanting to scratch. High itching complaint can also cause the anxiety level increased. The purpose of this study was to determine the effectiveness of Garra Rufa Care pruritus elderly who live in the village area, Indonesia This study was designed as a quasy experiment using non-probability techniques with a simple random sampling method. The respondents of this study consisted of 40 elderly people who had pruritus caused by dermatology and were divided into an experimental group and a control group. The independent variable was Garra Rufa Care, and the dependent variable was elderly with pruritus. This instrument of the study used the Numeric Rating Scale (NRS), Geriatric Anxiety Inventory (GAI) and used the Wilcoxon and Mann Whitney test with ? <0.05 as data analysis. The results showed the effect of Garra Rufa Care on itching complaint (p = 0,000) and there was a significant low (? = 0.014). The results showed the effect of Garra Rufa Care on anxiety level (p = 0,000) and there was a significant significance (? = 0,000). Psychological effect have given “micro massage” and decreased the anxiety level which have physically reduced itching scores. Garra Rufa was effectively used as an intervention in the elderly with pruritus by decreasing itching complaint and anxiety level. Further study was expected to replicate similar studies with more samples and carried out observation after making intervention.